ВИЗУАЛЬНЫЙ ОБРАЗ КОСТЮМА: ФИЛОСОФИЯ МОДЫ В ВИЗУАЛЬНЫХ ИССЛЕДОВАНИЯХ - ЦАРЕВСКАЯ, Е. Ю. (Вісник Харківського національного університету імені В. Н. Каразіна. Серія «Теорія культури і філософія науки», 2015)
Проблема исследования феномена моды и индустрии моды заключается в том, чтоосновная база исследовательских материалов предыдущих лет (это прежде всегосоциологические и семиотические) не раскрывают в полной мере сущности этогофеномена. Поэтому актуальным на данный момент является смещение акцента ввизуальное поле, и таким образом, междисциплинарное и более широкое. Т.к. индустриеймоды образец создается виртуально, не как вещь, а как образ, имеет местотипологизации визуального модного образа.Царевська О.Ю. ВІЗУАЛЬНИЙ ОБРАЗ КОСТЮМУ: ФІЛОСОФІЯ МОДИ УВІЗУАЛЬНИХ ДОСЛІДЖЕННЯХ Проблема дослідження феномена моди та індустріїмоди полягає в тому, що основна база дослідницьких матеріалів попередніх років (ценасамперед соціологічні та семіотичні) не розкривають повною мірою сутності цьогофеномена. Тому актуальним на даний момент є зміщення акценту в візуальне поле, ітаким чином, міждисциплінарне і більш широке. Т.я. індустрією моди зразокстворюється віртуально, не як річ, а як образ, має місце типологізації візуальногомодного образу.Ключові слова: індустрія моди, модний образ, візуальність, фатіческій модний образ,образ-інсталяція, подіумний образ.Tsarevska E.U. VISUAL IMAGE OF COSTUME: PHILOSOPHY OF FASHION IN THEVISUAL STUDIES Each of the classical concepts reflected the social nature of fashion as it wasin a certain era. The modern fashion is a specific phenomenon, that appears as industry.Fashion like industry is specialized production of modern and original models which isorganized on the principles of rationality. Understanding of what is produced not an actualmodel, but trendy - modernity and originality becomes essential. They express, respectively, thedesire for otherness, identity, on the one hand, and general following for all "spirit of the time"on the other. The fashion industry has created a virtual model, not as a thing, but as an image.This situation is similar to what J. Bodriiar describes, saying about the priority models ofreality. [2] In today's fashion world the spread of samples across reference groups aresimulated. The models in the magazines and TV ads are served not only as an object of a certainsize, color, texture, but as a desired image of social status, interpersonal relationships, etc.Photographers and designers are not so much concerned with showing all the features of themodel, but rather the creation around it the virtual social environment.By engaging in the process of changing fashion models, people not only acquire and usethings but bring the model into social reality. Fashion, as it becomes the industry, is thereproduction of social reality in the form of its simulation.Thus, by far the most extensive observations on the mechanism of fashion are accumulatedregarding to his external appearance and his costume. This fact LV Petrov explains in following:architecture, music, painting professionally are involved in small groups. The clothes are wornby all. That is why in the appearance of man the fashion is most clearly and visibly, and isuniversal [13, p.4].During this period, fashion has been studied mainly as a mass communication process,because in the operation mode involves in its sphere large groups of people and fashionmessages occur with the use of technical means of information reproduction (press, radio,television, film).B.D.Parygin sees fashion as a specific and dynamic form of standardized mass behavior thatoccurs mostly spontaneously under the influence of the dominant attitudes in society and rapidlychanging tastes and hobbies. The author considers the etymology of the fashion and comes to theconclusion that the etymological definition of fashion does not reveal its social essence, but itshows that the concept of fashion is socio-historical.Although the word "fashion" has penetrated into all the European languages, but it hasfailed to dislodge them from the other words related to it within the meaning of "taste", "fancy","style", "hobby", and others. Therefore Parygin considers necessary to consider the relationshipof concepts of fashion and taste, custom, culture, and advertising. The results of this review are:taste as a type of fashion let people in ancient times to give subjects of aesthetic appreciation ofhis work. Fashion - on the one hand, is the stage in the development of mass taste, and on theother hand – is a form of development. Fashion - is a form of public taste that exists objectivelyregardless of our individual consciousness, taste. The structure of society influences on fashionand taste, stratifying them.In the mass consciousness of the everyday phenomenon of fashion it's often related only tothe specific cultural sphere - a sphere of clothing. Obviously, such an approach is due tovagueness of the concept of fashion, which, on the one hand, the meaning of some of thephenomena that are characterized by high variability in any culture, and on the other hand - thesame phenomenon only in culture clothing. Such inconsistency of meaning often leads todifferences in understanding the phenomenon of fashion. But the same problem we face, forexample, using the concept of "culture." On the one hand a culture understands all that man cando, all aspects of his activities, and the other - in this concept are invested purely ethical oraesthetic sense.Key words: Fashion industry, visual Studies, fashionable image, phatic fashionable image,image-installation, podium image, semiotics.